Mechanical properties of γ-graphyne nanotubes. Issue 28 (25th April 2018) - Li, Maoyuan; Zhang, Yingming; Jiang, Yunliang; Zhang, Yun; Wang, Yunming; Zhou, Huamin
Abstract : The effects of the dimensions, temperature, strain rate and the presence of a vacancy on the mechanical properties of γ-GNTs were systematically investigated using MD simulations. Abstract : γ-Graphyne nanotubes (γ-GNTs), which are formed by rolling up a γ-graphyne sheet in a similar way to carbon nanotubes, exhibit unique mechanical properties due to the carbon atoms in the sp and sp 2 hybridized states. In this study, the mechanical properties of γ-GNTs were investigated using molecular dynamics simulations. The effects of the dimensions, temperature, strain rate and the presence of a vacancy on the mechanical properties, i.e., Young's modulus, fracture strength and fracture strain, were comprehensively studied. The results indicate that the mechanical properties of the γ-GNTs are not sensitive to the length and strain rate, while the Young's modulus increases with increasing diameter. Meanwhile, an obvious temperature-dependent mechanical behavior was also found due to the stronger thermal vibration of the atoms at a higher temperature, especially in terms of the fracture strength and fracture strain. In addition, the mechanical properties of the γ-GNTs would be degraded with the existence of a vacancy, and they are more sensitive to the vacancy in the benzene rings than that in the acetylenic linkages, especially for the double-vacancy. The underlying mechanisms were analyzed from the stress distribution and fracture structure during tensile deformation.